A Prospective Case-Controlled Study of Endothelial Function in Patients with Mild to Moderate Psoriasis (Annals of Medical Research, 2021)
Aim: The aim of this study is to investigate endothelial dysfunction in psoriasis patients with non-invasive methods.Materials and Methods: Fifty-three psoriasis patients and 53 healthy individuals were included in the study. Carotid artery intimae-media thickness and brachial artery flow-mediated dilation was measured both in patient and control groups.Results: Mean age, gender, body mass index, smoking habits, anthropometric measurements and arterial blood pressure values were similar in both groups. Mean psoriasis area and severity index score of psoriasis patients was 6.35±6.81. Triglyceride level was significantly higher (p0.05) and high density lipoprotein cholesterol level was significantly lower (p 0.05) in psoriasis patients when compared with the controls. Insulin resistance was found to be statistically higher in psoriasis patients group than the control group (p0.05); but flow-mediated dilation was found to be statistically significantly lower in psoriasis patients than the control group (p0.05). FT3 level was also found to be statistically significantly lower in psoriasis patients than the control group (p=0.05).Conclusion: This study showed endothelial dysfunction and insulin resistance in psoriasis patients with low disease activity even in the absence of clinical cardiovascular disease. Thyroid function tests could supply information about cardiovascular risk.
Keywords: Psoriasis; Endothelial Dysfunction; Free T3.